Evaluasi Kinerja Simpang Bersinyal Jl. Arief Rahman Hakim-Jl. Klampis Anom-Jl. Klampis Jaya Surabaya - Kartika Ayu Widyaningrum; R. Endro Wibisono (UM Purwokerto Press, 2021)
The intersection between Arief Rahman Hakim Street, Klampis Anom Street, Klampis Jaya Street is a signalized intersection with a high-density level due to trip generation and attraction. The low level of knowledge and culture of traffic is the phenomenon of vehicle congestion at the intersection involving many actors as the cause. This study aimed to determine the traffic performance of the signalized intersection at the Arief Rahman Hakim Street, Klampis Anom Street, Klampis Jaya Street at this point as well as to predict the traffic performance of the signalized intersection on the Arief Rahman Hakim Street,Klampis Anom Street, Klampis Jaya Street in 2024. The results of the performance evaluation of the signalized intersection on the Arief Rahman Hakim Street, Klampis Anom Street, Klampis Jaya Street was for the standard degree of saturation received in 2021; it was 4.33 in the north, 0.23 in the south, 3.17 in the east, and 2.98 in the west. In 2024 it will be 4.96 in the north, 0.36 in the south, 3.49 in the east, and 3.41 in the west. In 2024 the rate of population growth and the need for private vehicles will increase greatly.